Differences In Dimensional Stability of Type III Gypsum (Dental Stone) Usimg Potassium Sulfate and Without Adding Potassium Sulfate - Daniswara, Bimantara; Benyamin, Benni; Sugiarto, Febia Astiawati (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: Gypsum is a material widely utilized in dental medicine for imprinting study models in prosthesis manufacturing. Dimensional stability is a crucial requirement for achieving optimal gypsum imprints. The addition of potassium sulfate to type III gypsum may serve as a solution to enhance dimensional stability. This study aims to compare the dimensional stability values of type III gypsum with the addition of 4% potassium sulfate against type III gypsum without the addition of potassium sulfate.Methode: This research employs an experimental design with a post-test-only control group. A total of 32 specimens were produced using gypsum molds in accordance with ADA no. 19. The specimens were divided into two groups: the first group consisting of type III gypsum with added potassium sulfate, and the second group comprising type III gypsum without added potassium sulfate. Data were subjected to non-paired parametric t-tests.Result: The mean value for the type III gypsum group without potassium sulfate addition was 0.0288±0.00052%, while the mean value for the type III gypsum group with potassium sulfate addition was 0.0058±0.00040%. The non-paired t-test results revealed a p-value of 0.000.Conclussion: Based on the conducted research, the addition of potassium sulfate to type III gypsum resulted in enhanced dimensional stability.